Effect of Low Temperatures on Morphology of Alginate Microcarriers - Narozhnyi, Stanislav; Bobrova, Olena; Kovalenko, Igor (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):288